Analgesic Effect Study of Young Coconut Water (Cocos nucifera L.) on Mice (Mus musculus) Induced with Pain using Acetic Acid - Dini Indah Berlianti; Danti Nur Indiastuti; Gondo Mastutik; Shaohong Lai (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Pain signals tissue damage that is capable of reducing thequality of life. Non-Steroidal Anti-inflammatory Drugs (NSAIDs) are known as effective analgesic drugs which have various side effects, therefore natural minerals are used as an alternative medicine for pain and inflammation, one of which is known to be coconut water. Hence this research was conducted to find out the differences of the analgesic effect between young coconut water (Cocos nucifera L.) with non-selective and COX-2 selective NSAID on mice induced with pain from acetic acid 0.6% 1 ml/100gBW of mice.Methods: True experimental, conducted at the Pharmacology Laboratory in Faculty of Medicine of Airlangga University involving the sample of 48 mice (6 groups). The recorded data was tested using the oneway ANOVA methodology before then continued with the posthoc test of LSD.Results: The addition of young coconut water (Cocos nucifera L.) with the dosage of 3 ml/100gBW, 4 ml/100gBW, and 4.5 ml/100gBW of mice doesn't give any significant analgesic effect even though the analgesic protection percentage increases accordingly to its dosage (12.32%, 18.72%, 26.88%), but non-selective and COX-2 selective NSAID give significant analgesic effect (p<0.05) on mice induced with pain from acetic acid 0.6% 1 ml/100gBW of mice.Conclusion: There are differences in the analgesic effect of young coconut water (C. nucifera L.) with non-selective and COX-2 selective NSAID on mice induced with pain from acetic acid 0.6% 1 ml/100gBW of mice.